1999
DOI: 10.1128/iai.67.10.5367-5371.1999
|View full text |Cite
|
Sign up to set email alerts
|

Development of Antibodies against Chondroitin Sulfate A-AdherentPlasmodium falciparumin Pregnant Women

Abstract: In areas where Plasmodium falciparum is endemic, pregnant women are at increased risk for malaria, and this risk is greatest during the first pregnancy. The placenta sequesters parasites that are able to cytoadhere to chondroitin sulfate A (CSA), a molecule expressed by the placental syncytiotrophoblast, while parasites from a nonpregnant host do not bind to CSA. Cytoadherence is mediated by the expression of variants of the P. falciparum-erythrocyte membrane protein 1 family. Each member of this molecule fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…This could be explained by the fact that acquisition of immunity to malaria increases with successive pregnancies. Such immunity is thought to be due either to priming of memory T cells or to production of antibodies against P. falciparum chondroitin sulfate A (PfCSA) that prevent parasites' sequestration in the placenta [15,16,21]. The study also indicated that malaria parasite density decreased with increasing parity and age further reinforcing the belief that the ability to control malaria parasitemia is parity and/or agedependent.…”
Section: Discussionmentioning
confidence: 84%
“…This could be explained by the fact that acquisition of immunity to malaria increases with successive pregnancies. Such immunity is thought to be due either to priming of memory T cells or to production of antibodies against P. falciparum chondroitin sulfate A (PfCSA) that prevent parasites' sequestration in the placenta [15,16,21]. The study also indicated that malaria parasite density decreased with increasing parity and age further reinforcing the belief that the ability to control malaria parasitemia is parity and/or agedependent.…”
Section: Discussionmentioning
confidence: 84%
“…5 Sequestration of malaria parasites in the placenta may contribute to hypertensive diseases of pregnancy by reducing placental perfusion and oxidative stress, and exacerbating the placental changes associated with preeclampsia. 6 A hospital study in Dakar also suggested a causal link between malaria and hypertensive diseases of pregnancy; pre-eclampsia was more common in the rainy season, and women presenting with a malaria-infected placenta had a three-fold increase in the risk of pre-eclampsia compared with women whose placenta was not infected. 7 However, severe anemia during the rainy season due to nutritional deficiencies but also malaria could contribute to direct maternal mortality by complicating an obstetrical condition.…”
Section: Discussionmentioning
confidence: 99%
“…During pregnancy, a combination of adhesion to specific placental receptors and immune pressure selects for novel or rare IE variants that evade existing immunity. 10 Prior to, or at the commencement of the first pregnancy, individuals have lower levels of antibodies to variant surface antigens (VSA) expressed by placental isolates and CSA-binding IEs, 5,[11][12][13] compared with other isolates. After exposure in pregnancy, most women develop antibodies to these variants, 14,15 which are associated with reduced risk of maternal malaria and complications in some studies.…”
Section: Introductionmentioning
confidence: 99%